Papillary thyroid microcarcinoma: optimal management versus overtreatment. Issue 1 (January 2020) - Walgama, Evan; Sacks, Wendy L.; Ho, Allen S.
Abstract : Purpose of review: The treatment of small, low-risk papillary thyroid carcinoma has undergone a paradigm shift, with many tumors now initially treated with active surveillance rather than upfront surgery. Further studies on patients enrolled in active surveillance have refined our knowledge of the clinical behavior of papillary thyroid microcarcinomas. Recent findings: This article summarizes the major conclusions of landmark trials that launched active surveillance as a viable treatment option for selected patients. We discuss patient factors such as age and tumor size, the assessment of candidates for active surveillance, barriers to acceptance of active surveillance, quality of life issues, and economic considerations. Summary: Active Surveillance is a viable first-line treatment option for select papillary microcarcinomas.